Acting up : gender and theatre in India, 1979 onwards - Maṅkai, A.
Theatre is about representation, about individual bodies, and the way these bodies relate to, reflect, subvert and remake social bodies. Acting Up: Gender and Theatre in India, 1979 Onwards explores these intersections of gender and theatre through an examination of the work of women theatre practitioners. It looks at the conditions that shape these processes: feminist and class politics, caste, ethnicity, faith, and nationalism. This book thinks through a new feminist idiom for contemporary theatre practice. By examining the conditions of actual production of theatre work, often by a collective effort not tied to any single point of authority (text, playwright or director), this study gestures towards an alternate aesthetic framework. Acting Up analyses the work of a number of major theatre makers, including Amal Allana, Anuradha Kapur, Kirti Jain, Maya Rao, Moloyashree Hashmi, Neelam Mansingh Chowdhry, Sabitri Debi, Saoli Mitra, Saroop Dhruv, Sushama Deshpande, Triuprari Sharma, Usha Ganguli, Veenapani Chawla, and others, as well as theatre groups, such as Chennai Kalai Kuzhu, Jana Natya Manch, Theatre Union, Voicing Silence, etc. The author, A. Mangai, herself a leading feminist theatre maker, brings the practitioner's perspectives and insights, as well as her vast experience to bear upon this groundbreaking study.